Effect of Immediate Feedback and Delayed Feedback on Freestyle Swimming Skills Mastery - Cahya Fatimah Akbar; Ricky Wibowo; Lukmanul Haqim Lubay (Universitas Pendidikan Indonesia, 2022)
This study aimed to determine the effect of immediate feedback and delayed feedback on the front crawl swimming skill mastery. This study used a Two Group Pre-test Post-test research design. The results of this study showed that there was a significant effect of providing immediate feedback and delayed feedback on the front crawl swimming skill mastery. This study concludes that there is a significant effect of providing an immediate feedback and delayed feedback on front crawl swimming skill mastery, where immediate feedback is better for helping acquire front crawl swimming skills. For this reason, it should be a concern for educators, both Physical Education teachers and sport coaches, so that the learning process becomes effective and learning objectives can be achieved.